Understanding obsessive-compulsive disorder - literature review - Piasek, Laura; Szafran, Adrianna; Wiśniewska, Klaudia; Ostańska, Agnieszka; Terelak, Wiktor; Ciechański, Marcin; Witkowska, Edyta; Godek, Grzegorz; Więcław, Kacper; Stańko, Katarzyna (Journal of Education, Health and Sport, 2023)
Introduction: Obsessive-compulsive disorder can decrease the quality of life and is often experienced by patients throughout their lives. They involve the presence of obsessions (persistent, unwanted thoughts) and compulsions (actions/rituals performed by the patient to alleviate the discomfort associated with the obsessions). Currently, they are diagnosed based on the criteria of DSM-5. Aim of the study: The aim of this study is to review and analyze the available literature on obsessive-compulsive disorders. Materials and methods: A review of the literature available in the PubMed and Google Scholar databases on obsessive-compulsive disorders was conducted. Results: The exact cause of OCD remains unknown. The involvement of genetic and environmental factors is suspected. It has been shown that damage to certain brain structures due to injury or neurodegenerative diseases can lead to the development of obsessions and/or compulsions. The severity of symptoms is influenced by cognitive inflexibility, a high sense of responsibility, and magical thinking. Currently, pharmacotherapy and/or psychotherapy form the basis of treatment. The portrayal of individuals with OCD has been present in history and art for centuries. Summary: Aspects, causes, and treatment methods of OCD are still being investigated and discovered. Presenting this disorder through art can positively impact awareness and social acceptance.